2003
DOI: 10.1093/ndt/18.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tubular enzymuria facilitates early detection of acute renal impairment in the intensive care unit

Abstract: Tubular enzymuria on admission to the ICU is useful in predicting ARF. The cheapness and wide availability of automated assays for gamma GT and AP suggests that estimation of these enzymes in random urine samples may be particularly useful for identifying patients at high risk of ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
219
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(242 citation statements)
references
References 22 publications
10
219
0
13
Order By: Relevance
“…23,39,40 It is expressed on the surface of polymorphonuclear leukocytes and in several organs, including the kidney, in which it is localized, with a high density, on the brush border of proximal tubular CLINICAL RESEARCH www.jasn.org cells and on the cell surface of glomerular podocytes. 41,42 Debiec et al 42,43 showed that NEP may represent the target antigen in a rare subset of patients with alloimmune antenatal membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…23,39,40 It is expressed on the surface of polymorphonuclear leukocytes and in several organs, including the kidney, in which it is localized, with a high density, on the brush border of proximal tubular CLINICAL RESEARCH www.jasn.org cells and on the cell surface of glomerular podocytes. 41,42 Debiec et al 42,43 showed that NEP may represent the target antigen in a rare subset of patients with alloimmune antenatal membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine was estimated by Jaffe"s method using commercial reagent kit and α -GST was estimated in all the urine samples by colorimetric kinetic assay using NBD-Cl [18].…”
Section: B Evaluation Of the Temporal Pattern Of Serum Creatinine Anmentioning
confidence: 99%
“…Hence we designed this study to evaluate the efficiency of renal tubular cell specific enzyme α-Glutathione-s-transferase(α-GST) as a predictor of kidney injury in cancer patients treated with cisplatin, by studying the urinary excretion of alpha-GST at different time intervals and by comparing that with the changes in serum creatinine in cisplatin treated patients Cell specific biomarkers can predict toxic insults earlier and can provide information on sites of injury. Hence the urinary levels of α-GST, studied in a timely manner may help in identifying patients who may benefit from early interventions thus reducing the rate of morbidity and mortality associated with kidney injury [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although advances in medicine have improved outcomes in these fields, the concept of the golden hour remains loosely applied and increasingly investigated in the setting of AKI. With recent advances in critical care nephrology, including consensus definitions, improved risk stratification, and biomarkers, intensivists and nephrologists are ideally positioned to investigate how best to improve patient outcomes and decrease the severity of renal damage in the golden hours of early AKI (4-6).In the past, AKI research has focused on the earlier identification of AKI before the rise in serum creatinine or drop in urine output (7,8). Recently, investigators have shifted their focus beyond simply replacing serum creatinine with a new gold standard and have sought to augment the information provided by serum creatinine and urine output, combining them with biochemical biomarkers, functional assessment of urine-making capacity, or both (9-11).…”
mentioning
confidence: 99%
“…In the past, AKI research has focused on the earlier identification of AKI before the rise in serum creatinine or drop in urine output (7,8). Recently, investigators have shifted their focus beyond simply replacing serum creatinine with a new gold standard and have sought to augment the information provided by serum creatinine and urine output, combining them with biochemical biomarkers, functional assessment of urine-making capacity, or both (9-11).…”
mentioning
confidence: 99%